Oxidative Stress Status in Sera, Seminal Plasma and their Correlation with Lead (Pb) and Cadmium (Cd) in Iraqi Infertile Male - Suha Hanoon Hasan (Journal of Global Pharma Technology, 2016)
Oxidative stress has been identified as a major mediator in various etiologies of male infertility. Lead and cadmium are two of the well-known reproductive toxicants to which human are exposed occupationally and environmentally. These heavy metals can lead to negative effects on the testicular functions. The aim of the current study is to look for the differences in the oxidative stress status in serum and seminal plasma of infertile male patients (oligo, azoospermia) groups compared to that of fertile healthy (control) group and to evaluate lead and cadmium levels in sera and seminal plasma of these groups in comparison to fertile healthy controls. The correlation between their level in seminal plasma and serum was also investigated. The current study included three groups of Iraqi male, 32 infertile patients with oligospermia, with 32 infertile patients with azoospermia, and 37 fertile healthy as a control group. The measured parameters included serum and seminal plasma total oxidant status (TOS), total antioxidant capacity (TAC), oxidative stress index (OSI), lead and cadmium concentration. The results in comparison with that of the control groups showed:-A highly significant increase differences in serum (TOS), (OSI), Pb, and Cd in serum of all infertile groups and between them.A significant decrease in serum TAC of azoospermia group, as well as a significant decrease in serum TAC of oligospermia group with significant differences between these two patients groups.No significant differences in seminal plasma TOS, TAC, and OSI in all of the infertile groups.In seminal plasma, a highly significant decrease in Cd and Pb of azoospermia group. Meanwhile a highly significant decrease in Pb of oligospermia group with highly significant differences between them. The results showed no correlation in the measured parameters between serum and seminal plasma of both studied patients.The Personal correlation analysis of TOS, TAC, OSI, Cd, and Pb revealed the presence of: - in oligospermia group, a strong negative correlation was found between serum, (TOS&TAC), and (TAC&OSI), meantime strong positive correlation between (TOS&OSI) also noticed. In serum azoospermia group a positive correlation between TOS&OSI and negative correlation between TAC &OSI were found. Meanwhile in seminal plasma a negative correlation was found between OSI&TAC. Furthermore, the result revealed, that the non-significant inverse relationship exists between lead and Cadmium concentration in serum and the number of sperm.Keywords: Male infertility, Serum & Semen, Total oxidant status, Total antioxidant capacity, Oxidative stress index, lead, Cadmium.